Effects of Plant Growth Regulators on Biomass, Number of Nodes, Internodal Length and Leaf Water Relative Content of Fagopyrum esculentum Moench of Himalayan Region - Jamwal, Komal; Bhattacharya, Sujata; Puri, Sunil (International Journal of Economic Plants, 2021)
An experiment was carried out to access the effect of plant growth regulators (PGRs) on biomass, number of nodes, internodal length and leaf water relative content of Fagopyrum esculentum. Four major hormones: Indole Acetic Acid (IAA), Benzylaminopurine (BAP), Abscisic Acid (ABA) and Gibberellic Acid (GA) were used in combinations i.e. IAA+BAP, IAA+ABA, IAA+GA, ABA+BAP, BAP+GA and ABA+GA in concentration of 25, 50 and 100 mg l-1 through foliar spray. Results revealed that higher concentration of IAA+BAP (50 and 100 mg l-1) enhanced number of nodes and shoot fresh weight. Combination of BAP+GA at 100 mg l-1 concentration enhanced shoot fresh and dry weight. Root fresh and dry weight was improved in IAA+GA 100 mg l-1 treatment. Maximum relative water content was observed at 50 mg l-1 of ABA+GA concentration. No. of nodes and internodal length decreased in plants treated with ABA+GA (25 mg l-1). Combination of ABA+BAP at 25 mg l-1 concentration reduced internodal length and 100 mg l-1 affected root fresh as well dry weight. 25 mg l-1 concentration of BAP+GA lowered leaf relative water content, root fresh and dry weight. ABA in combination with IAA (ABA+IAA) at 25 mg l-1 negatively affected shoot fresh as well as dry weight.